(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
This paper sheds some light on the political situations in the region of Cyrenaica in the Ptolemaic period of 322 - 97 BC; it also deals with the political conflict on power between the Aristocratic party and Democratic party and the annexation of the region under the Ptolemaic monarchy. It also deals with the political and constitutional system that the Ptolemies had passed to rule the region and the relationships that were prevailed between the region and the Ptolemaic Egypt